Phenylpropanoids from red kohlrabi sprouts inhibits nitric oxide production in RAW 264.7 macrophage cells - Lee, Jae-Woong; Lee, Dae-Young; Baek, Dong-Ryeol; Jeong, Rak-Hoon; Lee, Dong-Sung; Kim, Youn-Chul; Kim, Geum-Soog; Baek, Nam-In; Lee, Youn-Hyung (Food science and biotechnology, 2014)
The sprouts of red kohlrabi ( Brassica oleracea var. gongylodes ) were extracted with methanol, and the concentrated extracts were successively partitioned with ethyl acetate, n -butyl alcohol ( n -BuOH), and H 2 O. From the n -BuOH fraction, four phenylpropanoids were isolated through repeated silica gel and ODS column chromatographies. On the basis of physico-chemical and spectroscopic data including NMR, MS, and IR, the isolated compounds were identified as 3-(3,4,5-trimethoxyphenyl)-2 E -propenoic acid methyl ester ( 1 ), ( E )-sinapic acid methyl ester ( 2 ), ( E )-sinapoyl glucoside ( 3 ), and lawsoniaside B ( 4 ). Moreover, the compounds dose-dependently inhibited NO production in RAW 264.7 cells with IC 50 values of 41.22 ( 1 ), 38.32 ( 3 ), and 22.65 ( 4 ) μM, respectively. With further studies, these compounds may be potentially useful in developing new anti-inflammatory agents.